The Riddle of Cantinflas : Essays on Hispanic Popular Culture, Revised and Expanded Edition - Stavans, Ilan (Book collections on Project MUSE., 2012)
"Ilan Stavans's collection of essays on kitsch and high art in the Americas makes a return with thirteen new colorful conversations that deliver Stavans's trademark wit and provocative analysis. "A Dream Act Deferred" discusses an issue that is at once and always topical in the dialogue of Hispanic popular culture: immigration. This essay generated a vociferous response when first published in The Chronicle of Higher Education as the issue of immigration was contested in states like Arizona, and is included here as a new addition that adds a rich layer to Stavans's vibrant discourse. Fitting in this reconfiguration of his analytical conversations on Hispanic popular culture is Stavans's "Arrival: Notes from an Interloper," which recounts his origins as a social critic and provides the reader with interactive insight into the mind behind the matter. Once again delightfully humorous and perceptive, Stavans delivers an expanded collection that has the power to go even further beyond common assumptions and helps us understand Mexican popular culture and its counterparts in the United States."--Project Muse.